Investors' environmental guidelines : Bulgaria, Czech Republic and Slovak Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania /: Bulgaria, Czech Republic and Slovak Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania. (1994) - Unknown
No abstract available